1999
DOI: 10.1021/jm990139o
|View full text |Cite
|
Sign up to set email alerts
|

Substrate Specificity and Stereoselectivity of Rat Brain Microsomal Anandamide Amidohydrolase

Abstract: In Table 2, the IC 50 's of compounds 3 and 4 should be switched: compound 3, >50 a ; compound 4, 13.3 a .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
52
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(55 citation statements)
references
References 0 publications
3
52
0
Order By: Relevance
“…2). It is interesting to note that the enantioselectivity for anandamide transport displayed by 20 and 21 and 33 and 34 is congruent to that demonstrated for anandamide amidohydrolase, but opposite to that for the CB1 receptor (20,25).…”
mentioning
confidence: 71%
“…2). It is interesting to note that the enantioselectivity for anandamide transport displayed by 20 and 21 and 33 and 34 is congruent to that demonstrated for anandamide amidohydrolase, but opposite to that for the CB1 receptor (20,25).…”
mentioning
confidence: 71%
“…Moreover, endogenous amide hydrolases do not readily cleave fatty acyl tertiary amides, i.e. those with two substitutions on the amide nitrogen (18). Thus, attaching the cage to the amide nitrogen of VNA should generate a caged molecule that is both biologically inactive and resistant to enzymatic degradation.…”
Section: Resultsmentioning
confidence: 99%
“…This was somewhat surprising, given the broad range of acyl amides and acyl esters that can be hydrolyzed by FAAH (3). On the other hand, previous studies demonstrated that substitutions at the ␣-position of the acyl chain of primary amide or anandamide analogue compounds rendered the compound resistant to hydrolysis by FAAH (39,40). The incorporation of a bulky phenoxy-group near the amide moiety may serve a similar structural hindrance to the enzyme's active site and restrict hydrolysis.…”
Section: Discussionmentioning
confidence: 99%